Problems of Mediation by Judges against Divorce Cases in Gorontalo Religious Court Class 1A - Ayub Wahidun Muntholib (Estudiante Law Journal, 2021)
The purpose of this study was to determine what factors influence the mediation process in the settlement of divorce cases at the Gorontalo Religious Court Class 1A. The type of research used is Sociological Juridical research, using data types consisting of primary data, secondary data, and tertiary data. Data collection techniques were carried out using interviews, observation, and library techniques. Then the data were analyzed descriptively and provided an overview or explanation of the subject and object of research as the results of the research conducted. The results of this study indicate that the problem with the delay in the mediation process for divorce cases at the Religious Courts of Gorontalo City Class 1A is caused by several factors including the desire of the parties, namely to be clean and hard to choose divorce, so the parties do not have good faith to resolve the dispute peacefully, the openness factor which is usually influenced by the shame and prestige of the parties to reveal personal problems in the mediation process, the mediator factor in the sense that the imbalance between the incoming mediation cases and the human resources in the Gorontalo religious court class 1A. based on data in 2021 there are 153 mediation cases but the available human resources are only 8 Judges and mediators so it will be difficult to handle with limited human resources, and environmental factors in the sense that the parties become discouraged and feel prestige when deciding to make peace because if this party made an amicable decision while the case was already in court, they were worried that they would become a laughing stock and also become the subject of stories by friends from both sides.